2014
DOI: 10.1208/s12248-014-9667-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug Clearance in Children: an Evaluation of the Predictive Performance of Several Models

Abstract: The objective of this study is to evaluate the predictive performance of several models to predict drug clearance in children ≤5 years of age. Six models (allometric model (data-dependent exponent), fixed exponent of 0.75 model, maturation model, body weight-dependent model, segmented allometric model, and age-dependent exponent model) were evaluated in this study. From the literature, the clearance values for six drugs from neonates to adults were obtained. External data were used to evaluate the predictive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(111 citation statements)
references
References 43 publications
6
105
0
Order By: Relevance
“…The substantial prediction error introduced by exponent 0.75 in GFR observed in this study is in line with the observations noted in other studies for the prediction of drug clearances in the aforementioned age groups (4,38,40,41). In this study, however, it was observed that the predictive power of exponent 0.75 for GFR was comparable with other models in children >1 year of age (this will not be true for the prediction of drug clearances and generally exponent 0.75 provides a good prediction of drug clearances in children >5 years of age).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The substantial prediction error introduced by exponent 0.75 in GFR observed in this study is in line with the observations noted in other studies for the prediction of drug clearances in the aforementioned age groups (4,38,40,41). In this study, however, it was observed that the predictive power of exponent 0.75 for GFR was comparable with other models in children >1 year of age (this will not be true for the prediction of drug clearances and generally exponent 0.75 provides a good prediction of drug clearances in children >5 years of age).…”
Section: Discussionsupporting
confidence: 93%
“…Both these models have been proposed for the prediction of drug clearances in pediatrics (4,(8)(9)(10)(11). Although the BDE model was developed based on inulin clearance, the model's predictive power was comparable for GFR based on inulin and creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations